2015
DOI: 10.1186/s12884-015-0676-z
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic inequalities across a range of health status indicators and health behaviours among pregnant women in prenatal primary care: a cross-sectional study

Abstract: BackgroundSuboptimal maternal health conditions (such as obesity, underweight, depression and stress) and health behaviours (such as smoking, alcohol consumption and unhealthy nutrition) during pregnancy have been associated with negative pregnancy outcomes. Our first aim was to give an overview of the self-reported health status and health behaviours of pregnant women under midwife-led primary care in the Netherlands. Our second aim was to identify potential differences in these health status indicators and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 41 publications
4
56
0
7
Order By: Relevance
“…Our findings are in line with previous studies, which reported that smoking, including passive smoking, was the health behaviour most strongly associated with educational disparities, finding a higher percentage of smokers in groups of pregnant women with lower levels of education (19,23,24). Study Lu Y et al (2001) also reported that smokers with higher levels of education were more likely to stop smoking when they discovered they were pregnant, leading to even greater disparities in smoking (19,25). According to a cross--sectional study of pregnant women and new mothers from 15 European countries, which also included data from Slovenia, prevalence of smoking during pregnancy ranged from 18.9 % in Croatia to 4.2 % in Iceland (9).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are in line with previous studies, which reported that smoking, including passive smoking, was the health behaviour most strongly associated with educational disparities, finding a higher percentage of smokers in groups of pregnant women with lower levels of education (19,23,24). Study Lu Y et al (2001) also reported that smokers with higher levels of education were more likely to stop smoking when they discovered they were pregnant, leading to even greater disparities in smoking (19,25). According to a cross--sectional study of pregnant women and new mothers from 15 European countries, which also included data from Slovenia, prevalence of smoking during pregnancy ranged from 18.9 % in Croatia to 4.2 % in Iceland (9).…”
Section: Discussionsupporting
confidence: 93%
“…The correlation between lower maternal education and lower maternal age is expected because women increasingly delay childbirth in order to receive more education and take advantage of increased career opportunities created thereby (22). Our findings are in line with previous studies, which reported that smoking, including passive smoking, was the health behaviour most strongly associated with educational disparities, finding a higher percentage of smokers in groups of pregnant women with lower levels of education (19,23,24). Study Lu Y et al (2001) also reported that smokers with higher levels of education were more likely to stop smoking when they discovered they were pregnant, leading to even greater disparities in smoking (19,25).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, in a 2017 breakfast study, researchers reported that a high-fat/high sugar "toasted sandwich" and chocolate milk-type beverage caused reductions in hippocampal-dependent learning and memory in healthy young adults after only four days [61]. Skipping breakfast has also been linked to depression, anxiety and high levels of stress throughout the life course, and this is pronounced in association with socioeconomic disadvantage [62][63][64].…”
Section: Nutrition For Mental Cognitive Healthmentioning
confidence: 99%